Clonal Parental Effects on Offspring Growth of Different Vegetative Generations in the Aquatic Plant Pistia stratiotes - Zhang, Li-Min; Roiloa, Sergio R.; Zhang, Jia-Fan; Yu, Wen-Han; Qiu, Chen-Yan; Wang, Dan-Hao; Yu, Fei-Hai (Frontiers in Plant Science, 2022)
Parental (environmental) effects can modify the growth of offspring, which may play an essential role in their adaptation to environmental variation. While numerous studies have tested parental effects on offspring growth, most have considered offspring growth of only one generation and very few have considered offspring growth of different generations. We conducted a greenhouse experiment with an aquatic clonal plant Pistia stratiotes. We grew single ramet of P. stratiotes under low or high nutrients, the initial (parent) ramets produced three different generations of offspring ramets, and these offspring ramets were also subjected to the same two nutrient levels. High nutrients currently experienced by the offspring increased biomass accumulation and ramet number of all three offspring generations of P. stratiotes. However, these positive effects on biomass were greater when the offspring ramets originated from the parent ramets grown under low nutrients than when they were produced by the parent ramets grown under high nutrients. These results suggest that parental effects can impact performance of different offspring generations of clonal plants. However, heavier offspring ramets produced under high nutrients in parental conditions did not increase the subsequent growth of the offspring generations. This finding indicates that parental provisioning in favorable conditions may not always increase offspring growth, partly depend on root allocation but not ramet size such as ramet biomass.